IDENTIFIKASI PENGARUH AIR LINDI (LEACHATE) TERHADAP KUALITAS AIR DI SEKITAR TEMPAT PEMBUANGAN AKHIR (TPA) TANJUNG BELIT - Alfi Rahmi; Bambang Edison (Aptek, 2019)
Tanjung Belit landfill waste processing operations use a controlled landfil system, this is indicated by the presenceof garbage collection ponds and leachate collection channels, but in the rainy season there is difficulty in accessingroads causing waste to be dumped outside the garbage collection pond, so that the TPA applies an open dumpingsystem trash transported is immediately disposed of and stacked on land near the landfill. Waste deposits willproduce a liquid known as lindi (leachate). This study aims to identify the effect of leachate from Tanjung BelitLandfill (TPA) on water quality around Tanjung Belit landfill. Samples were taken as many as 5 samples, namelyleachate, monitoring well water and river water around the landfill where the parameters measured were pH, DO,TDS, BOD, COD, Nitrite, Sulphate and Chloride based on PP No. 82 of 2001 and KEPMEN LH No.51 of 1995concerning Liquid Waste Quality Standards. The results of the analysis show that the leachate of Tanjung Belitlandfill affects the quality of river water and monitoring well water around the Tanjung Belit landfill but is stillclassified as lightly polluted. The influence of distance on the quality of sunagi water and monitoring well water,namely the farther the distance, the less contamination in water.